The impact of depressive symptoms on patient–provider communication in HIV care - Jonassaint, Charles R. (2013)
Persons with HIV who develop depression have worse medical adherence and outcomes. Poor patient–provider communication may play a role in these outcomes. This cross-sectional study evaluated the influence of patient depression on the quality of patient–provider communication. Patient–provider visits (n = 406) at four HIV care sites were audio-recorded and coded with the Roter Interaction Analysis System (RIAS). Negative binomial and linear regressions using generalized estimating equations tested the association of depressive symptoms, as measured by the Center for Epidemiology Studies Depression scale (CES-D), with RIAS measures and postvisit patient-rated quality of care and provider-reported regard for his or her patient. The patients, averaged 45 years of age (range = 20–77), were predominately male (n = 286, 68.5%), of black race (n = 250, 60%), and on antiretroviral medications (n = 334, 80%). Women had greater mean CES-D depression scores (12.0) than men (10.6; p = 0.03). There were no age, race, or education differences in depression scores. Visits with patients reporting severe depressive symptoms compared to those reporting none/mild depressive symptoms were longer and speech speed was slower. Patients with severe depressive symptoms did more emotional rapport building but less social rapport building, and their providers did more data gathering/counseling (ps < 0.05). In postvisit questionnaires, providers reported lower levels of positive regard for, and rated more negatively patients reporting more depressive symptoms (p < 0.01). In turn, patients reporting more depressive symptoms felt less respected and were less likely to report that their provider knows them as a person than none/mild depressive symptoms patients (ps < 0.05). Greater psychosocial needs of patients presenting with depressive symptoms and limited time/resources to address these needs may partially contribute to providers’ negative attitudes regarding their patients with depressive symptoms. These negative attitudes may ultimately serve to adversely impact patient–provider communication and quality of HIV care.